Low-dose citalopram as a 5-HT neuroendocrine probe. - Attenburrow, M; Mitter, P; Whale, R; Terao, T; Cowen, P (2001)
RATIONALE: Intravenous administration of the selective serotonin re-uptake inhibitor, citalopram (20 mg), is known to increase plasma prolactin (PRL) and cortisol in human subjects. This suggests that citalopram may be a useful tool to probe brain serotonin function. OBJECTIVE: To find out whether lower doses of intravenous citalopram would be sufficient to increase plasma prolactin and cortisol. METHODS: Eleven subjects were tested on three occasions in a double-blind, cross-over design receiving: (a) placebo, (b) citalopram 5 mg and (c) citalopram 10 mg infused intravenously over a 30-min period. A further six subjects received intravenous citalopram (10 mg) on two occasions receiving in addition the 5-HT2A2C receptor antagonist, cyproheptadine (4 mg orally) or placebo, 6 h before each infusion in a double-blind, randomised, cross-over design. Plasma PRL and cortisol levels were measured before and for 150 min after the infusion. RESULTS: Citalopram increased plasma PRL and cortisol in a dose-related manner. Cyproheptadine lowered baseline PRL and cortisol but did not attenuate the endocrine responses to citalopram. Citalopram infusions were well-tolerated. CONCLUSIONS: Low-dose citalopram has potential utility as a neuroendocrine challenge test. The endocrine responses to citalopram are probably not mediated predominantly by 5-HT2A/2C receptors.